Three link robot control with fuzzy sliding mode controller based on RBF neural network - Ak, Ayca Gokhan; Cansever, Galip (IEEE, 2006)
The purpose of this paper is to propose adaptive fuzzy Sliding Mode Control (SMC) based on Radial Basis Function Neural Network (RBFNN) for trajectory tracking problem of three link robot manipulator. A RBFNN is used to compute the equivalent control of sliding mode control. A Lyapunov function is selected for the design of the SMC and an adaptive algorithm is used for weight adaptation of the RBFNN. Simulation results of three link Scara robot manipulator verify the validity of the proposed controller in the presence of uncertainties.
Keywords: Automation & Control Systems; Computer Science